Effect of Clearance on Residual Stress and Quality in Rolled Tube-Tubesheet Connections - Stovpnyk, Oleksandr V.; Kabat, Oleh S.; Ved’, Viktor V. (Вісник Приазовського Державного Технічного Університету, 2025)
ENG: The quality of the tube-to-tubesheet joint is a critical factor determining the reliability and durability of heat exchangers and various types of industrial equipment operating under demanding conditions. This article examines the influence of the clearance between the tube and the tubesheet hole on the magnitude of residual stresses in the joint following the tube rolling process. The experimental component of the study involved precise measurements of actual clearances using specialized tools, the calculation of residual stresses through the mechanical stress relief method, and a comprehensive statistical analysis of the collected data to ensure accuracy and consistency. The findings revealed that the actual clear-ance typically exceeds the nominal value specified in design standards, and an increase in this clearance directly corre-lates with a rise in residual stresses within the joint. Notably, the highest stress levels were observed at clearances of 0.40 mm and greater, which may lead to localized plastic deformation, compromising the structural integrity and reducing the fatigue strength of the joint over time. Based on the analysis, the optimal clearance range was determined to be between 0.10 mm and 0.30 mm, as it strikes a balance between ensuring joint reliability and maintaining acceptable stress levels, thus minimizing the risk of premature failure. To validate the reliability of the experimental results, advanced statistical methods were employed, including the calculation of standard deviation to assess data variability and the application of Student's t-test to evaluate the significance of the observed trends. These calculations confirmed a statistically significant relationship between clearance size and residual stress levels, with particularly pronounced effects observed in joints involving small-diameter tubes, where tolerances are more critical. The outcomes of this research have practical impli-cations for the design and manufacturing of shell-and-tube heat exchangers, offering a pathway to optimize joint param-eters, enhance operational performance, and extend service life. Additionally, the study provides detailed practical rec-ommendations for quality control, including precise methods for measuring clearances with highaccuracy and evaluating residual stresses during production and maintenance processes.

UKR: Якість з'єднання труба-трубна дошка відіграє ключову роль у забезпеченні надійності та довговічності теплообмінників і іншого промислового обладнання, що працює в складних експлуатаційних умовах. У даній статті досліджено вплив величини зазору між зовнішньою поверхнею труби та отвором у трубній дошці на рівень залишкових напружень у з'єднанні після процесу вальцювання. Експериментальна частина роботи включала ретельні вимірювання фактичних зазорів за допомогою спеціалізованого обладнання, розрахунок залишкових напру-жень методом механічного зняття напружень, а також детальний статистичний аналіз отриманих даних для підтвердження їх точності та достовірності. Результати дослідження показали, що фактичний зазор у біль-шості випадків перевищує номінальне значення, визначене проєктними стандартами, а його зростання призво-дить до суттєвого збільшення залишкових напружень у з'єднанні. Найвищі напруження фіксувалися при зазорах від 0,40 мм і більше, що може спричинити локальну пластичну деформацію, негативно впливаючина структурну цілісність і знижуючи втомну міцність з'єднання протягом тривалого часу. Оптимальний діапазон зазорів, який забезпечує баланс між надійністю з'єднання та допустимим рівнем напружень, встановлено в межах 0,10-0,30 мм, що дозволяє знизити ризик передчасного руйнування. Для перевірки достовірності даних використано су-часні методи статистичного аналізу, зокрема обчислення стандартного відхилення для оцінки розкиду резуль-татів і t-критерій Стьюдента для визначення статистичної значущості виявленихзакономірностей. Розраху-нки підтвердили тісний зв’язок між величиною зазору та рівнем залишкових напружень, особливо для труб ма-лого діаметра, де точність допусків має вирішальне значення. Отримані результати можуть бути застосовані під час проєктування та виробництва кожухотрубних теплообмінників, сприяючи оптимізації параметрів з'єд-нань, підвищенню ефективності роботи обладнання та подовженню терміну його служби. У статті також наведено практичні рекомендації щодо контролю якості, включаючи високоточні методи вимірювання зазорів і оцінки залишкових напружень на етапах виробництва та технічного обслуговування.
Вплив зазору на залишкові напруження та якість вальцьованих з'єднань труба-трубна дошка
Oleksandr V.Stovpnyk: ORCID 0000-0003-4391-6644; Oleh S. Kabat: ORCID 0000-0001-7995-5333; Viktor V. Ved’: ORCID 0000-0002-2391-6463
Keywords: tube rolling; residual stresses; clearance; quality control; process parameters; reliability; durability; вальцювання; залишкові напруження; зазор; контроль якості; параметри процесу; надійність; довговічність; КІІ; TECHNOLOGY; TECHNOLOGY:: Сontrol quality